Effectiveness of Organization Management Model in Private Higher Education under Hebei Province, China - Shaonan , Chen; Chanphong , Somsak; Howattanakul, Sutida (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were: (1) To study the components of effectiveness of organization management model in private higher education under Hebei Province. (2) To develop a model of effectiveness of organization management model in private higher education under Hebei Province. (3) To propose the guideline to improve effectiveness of organization management model in private higher education under Hebei Province. The research was a mixed methodology research. Population was included 9,723 teachers and administrators from 20 private higher educations under Hebei Province. The sample size was obtained by stratified sampling technique, totalling 370 teachers and administrators of private higher educations in Hebei Province. The 9 key informants were obtained by purposive sampling method. The instruments used for data collection were a semi-structured interview, a five-point rating scale questionnaire, and note taking by focus group discussion. The statistics used for data analysis were means, standard deviation, Average Variance Extracted, Composite Reliability and Confirmatory Factor Analysis. The research findings revealed that: (1) There were 5 components and 25 key variables of effectiveness of organization management model in private higher education under Hebei Province, which consisted of Organization objective, Organization communication, Organization incentive, Organization evaluation and Organization effectiveness; and (2) There were total 15 guidelines for effectiveness of organization management model in private higher education under Hebei Province.